Del-1, an Endogenous Inhibitor of TGF-β Activation, Attenuates Fibrosis - Kim, Dong-Young; Lee, Seung-Hwan; Fu, Yan; Jing, Feifeng; Kim, Won-Young; Hong, Sang-Bum; Song, Jung-A; Choe, Han; Ryu, Hyun Jin; Kim, Minjung; Lim, Dahae; Kim, Min-Seon; et al. (Frontiers in Immunology, 2020)
Uncontrolled activation of transforming growth factor (TGF)-β results in a wide range of pathologic conditions. Therapeutic interventions to regulate TGF-β signaling during fibrosis have been developed but the effectiveness is still limited. Here, we show that developmental endothelial locus-1 (Del-1) ameliorates fibrosis in mice by inhibiting αv integrin-mediated activation of TGF-β. Del-1 bound to αvβ6 integrin, an important activator of TGF-β, and inhibited the binding of αvβ6 integrin to the latency-associated peptide (LAP), thereby suppressing αv integrin-mediated activation of TGF-β. Lack of Del-1 increased colocalization of αv integrin and LAP in the lungs, which was reversed by Del-1 supplementation. The crucial role of Del-1 in regulating TGF-β activity was recapitulated in a mouse model of fibrosis using an adenovirus expressing inactive TGF-β1. Del-1 supplementation improved the pathological characteristics of the mice and reduced mortality. Thus, we propose that Del-1 is a negative regulator of TGF-β activation and a potential anti-fibrotic factor.